Lipiodol injections for optimization of target volume delineation in a patient with a second tumor of the oropharynx: A case report - Haderlein, Marlen; Merten, Ricarda; Stojanovic, Andrea; Speer, Stefan; Scherl, Claudia; Fietkau, Rainer; Ott, Oliver J. (Strahlentherapie und Onkologie, 2015)
Lipiodol injections were administered in the head and neck area to improve gross tumor volume (GTV) definition for small-volume re-irradiation of a 63-year-old previously irradiated patient with a second tumor of the oropharynx in the posterior wall with longitudinal ligament infiltration (cT4cN0cM0).The patient had dialysis-depending renal failure. On diagnostic computed tomography (CT), which was performed with intravenous contrast agent, the tumor in the oropharynx was not detectable. Because of dialysis-depending renal failure comorbidity, no contrast agent was applied in the planning CT and in the diagnostic magnetic resonance imaging (MRI) study. In each cross-sectional imaging study performed, the GTV, especially in craniocaudal extensions, was not safely delineable. Therefore, craniocaudal tumor margins were pharyngoscopically marked with Lipiodol injections, an iodine-containing contrast agent.In a second planning CT, the GTV could be defined with the help of the Lipiodol marks and small-volume re-irradiation was performed. No Lipiodol-associated side effects occurred in the patient.In the present case, the use of Lipiodol injections at the tumor margins facilitated the definition of the GTV.
EVALuna2:18277